Link Budget Analysis for Reconfigurable Smart Surfaces in Aerial Platforms - Safwan Alfattani (IEEE, 2021)
Non-terrestrial networks, including Unmanned Aerial Vehicles (UAVs), High Altitude Platform Station (HAPS) nodes and Low Earth Orbiting (LEO) satellites, are expected to have a pivotal role in sixth-generation wireless networks. With inherent features such as flexible placement, wide footprints, and preferred channel conditions, they can tackle several challenges faced by current terrestrial networks. However, their successful and widespread adoption relies on energy-efficient on-board communication systems. In this context, the integration of Reconfigurable Smart Surfaces (RSS) into aerial platforms is envisioned as a key enabler of energy-efficient and cost-effective aerial platform deployments. RSS consist of low-cost reflectors capable of smartly directing signals in a nearly passive way. In this paper, we investigate the link budget of RSS-assisted communications for two RSS reflection paradigms discussed in the literature, namely “specular” and “scattering” paradigms. Specifically, we analyze the characteristics of RSS-equipped aerial platforms and compare their communication performance with that of RSS-assisted terrestrial networks using standardized channel models. In addition, we derive the optimal aerial platform placements for both reflection paradigms. Our results provide important insights for the design of RSS-assisted communications. For instance, given that a HAPS has a large area for RSS, it provides superior link budget performance in most studied scenarios. In contrast, the limited RSS area on UAVs and the large propagation loss in LEO satellite communications make them unfavorable candidates for supporting terrestrial users. Finally, the optimal location of an RSS-equipped platform may depend on the platform's altitude, coverage footprint, and type of environment